2021
DOI: 10.1371/journal.pone.0246258
|View full text |Cite
|
Sign up to set email alerts
|

Stress reactivity near birth affects nest building timing and offspring number and survival in the European rabbit (Oryctolagus cuniculus)

Abstract: The physiological response to stressors has great importance, and its variance has an adaptive role in the survival of individuals. This study describes the effects of stress-axis activation on maternal behavior during the birthing process (parturition) in captive rabbits (Oryctolagus cuniculus). In this species, chances of survival are strongly influenced by nest quality. Thus, maternal care is initiated with nest preparation in late pregnancy, which itself is subject to strict and complex hormonal regulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…(Fajer et al, 1971). In case of wild rabbits, a positive correlation was also found between cortisol and progesterone values measured on the day of parturition (Benedek et al, 2021), which can be explained with a common metabolic pathway, as some progesterone is released into the bloodstream before it is converted to cortisol (Beaulieu-McCoy et al, 2017).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…(Fajer et al, 1971). In case of wild rabbits, a positive correlation was also found between cortisol and progesterone values measured on the day of parturition (Benedek et al, 2021), which can be explained with a common metabolic pathway, as some progesterone is released into the bloodstream before it is converted to cortisol (Beaulieu-McCoy et al, 2017).…”
Section: Discussionmentioning
confidence: 76%
“…Samples were stored at -20 °C until extraction. Cortisol and progesterone levels were measured from faeces based on their breakdown products using an RIA method according to Benedek et al, (2021). After freeze-drying, the samples were ground, homogenized, and mixed thoroughly.…”
Section: Hormone Assessmentmentioning
confidence: 99%
“…Studies in the domestic rabbit revealed that different elements of the behavioral sequence, such as digging, collection and carrying of nest material are under hormonal control (Zarrow et al1963;González-Mariscal et al, 2016). Furthermore, physiological state, genetic factors and individual's social environment, could conceivably alter the females'burrow and nest building behavior, modifying the timing of the hormonal signals involved (González-Redondo 2010; Benedek et al 2021).…”
Section: Nest Building Testmentioning
confidence: 99%
“…According to Benedek et al (2021), progesterone is one of the most dominant in the process of nest construction. The authors demonstrated that its level is altered by the level of cortisol elevation in the animal, which potentially influence the preparation of the nest for the newborn kittens.…”
Section: Nest Building Testmentioning
confidence: 99%
“…According to Benedek et al [ 53 ], 24 h after the pressure of stress the decomposition of the hormone cortisol appears in the feces.…”
Section: Introductionmentioning
confidence: 99%